DAMPAK PERSONAL SELLING TERHADAP PENCAPAIAN PENJUALAN KOMPUTER PADA CV. SHAHEEN GLOBAL PRODUCTION - Yahya Tanjung (Majalah Ilmiah METHODA, 2019)
Shaheen Global Production is a company that sells computers. Based on the results of the study, researchers revealed several problems in the implementation of their business activities, namely, not achieving sales targets and a decline in profits in two periods, namely 2017 and 2018. These problems are caused, lack of willingness or desire in employees to find new subscriptions, employees pay less attention to follow up in terms of contacting customers.The purpose of the research is to find out the implementation of personal selling, to find out the condition of computer sales, to find out how much influence personal selling has on the achievement of computer sales, to find out the obstacles faced in the implementation of personal selling and what efforts are being made in overcoming these obstacles. The research method used is descriptive analysis. Data collection techniques carried out by library research and field research in the form of interviews, non- participant observation and questionnaire distribution. For data analysis used validity test, reliability test, simple linear regression, Sperman rank correlation coefficient, hypothesis test, and the coefficient of determination. Based on the data obtained from the results of the study through the calculation of the spearman rank correlation coefficient showed a relationship with a strong category, the correlation results obtained with a value of 0.621, as for the hypothesis testing conducted by researchers obtained for tcount> ttable ie 3,8006> 2,069 means Hi accepted and Ho is rejected, besides that the coefficient of determination is 38.56% and the remaining 61.44% is obtained.Barriers experienced by CV. Shaheen Global Production, which is an understanding of the products offered by employees is still very weak because almost most of the education status of employees is only limited to high school, while the products offered by many companies use IT terms like a technology company, regarding time management, where employees other than doing process prospecting or finding new customers to achieve sales targets on the other hand employees must make contact with customers to ensure customer satisfaction. Suggestions that researchers can point out are, companies should recruit employees who play an important role in personal selling activities, at least those who have experience in product marketing, especially experience in technology, so that communication skills have been mastered and companies only provide direction, companies must expand the area sales, in addition the company must increase the number of personnel so that profitability can increase every year.